2020
DOI: 10.1093/ejo/cjaa031
|View full text |Cite
|
Sign up to set email alerts
|

The upper airway volume effects produced by Hyrax, Hybrid-Hyrax, and Keles keyless expanders: a single-centre randomized controlled trial

Abstract: Summary Objective To assess upper airway volume changes after rapid maxillary expansion (RME) with three different expanders. Trial design Three-arm parallel randomized clinical trial. Methods Sixty-six patients, 10–16 years old, in permanent dentition, with maxillary transverse deficiency were recruited and assigned with blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 57 publications
0
18
0
6
Order By: Relevance
“…The number of activations suggested was almost the same in all designs: in two studies, the screw was turned two times a day, for the first week, then the appliance was activated one time per day; the screw used was a 9 mm Hyrax for the TB group and a 9 mm Jackscrew for the MARPE TTB group [ 23 , 24 ]. In 11 studies suggested activating the screw two times a day until the finish of the expansion: the screws used in these cases were 9 mm Hyrax in the 9 TB group; a Hyrax miniscrew was used in the 1 TB group and 12 mm Hyrax jackscrew in the 1 TB group; one group used the Keles Keyless screw; in the MARPE TTB groups, two studies used 8 mm a miniexpander jackscrew and one study used a 12 mm jackscrew [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Two studies suggested one activation/day with the Hyrax screw [ 36 , 37 ], and the protocol was not determined in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of activations suggested was almost the same in all designs: in two studies, the screw was turned two times a day, for the first week, then the appliance was activated one time per day; the screw used was a 9 mm Hyrax for the TB group and a 9 mm Jackscrew for the MARPE TTB group [ 23 , 24 ]. In 11 studies suggested activating the screw two times a day until the finish of the expansion: the screws used in these cases were 9 mm Hyrax in the 9 TB group; a Hyrax miniscrew was used in the 1 TB group and 12 mm Hyrax jackscrew in the 1 TB group; one group used the Keles Keyless screw; in the MARPE TTB groups, two studies used 8 mm a miniexpander jackscrew and one study used a 12 mm jackscrew [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Two studies suggested one activation/day with the Hyrax screw [ 36 , 37 ], and the protocol was not determined in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there are two randomized controlled clinical trials, which have evaluated airway changes following RME treatment 11,12 . However, none of these studies included inactive control groups.…”
Section: Introductionmentioning
confidence: 99%
“…10 To our knowledge, there are two randomized controlled clinical trials, which have evaluated airway changes following RME treatment. 11,12 However, none of these studies included inactive control groups. Thus, the real influence of RME on nasal airway dimensions and functions, considering the influence of growth, has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Isso sugere um dos benefícios do Hyrax híbrido com relação à melhoria da respiração, como já foi mencionado por Motro et al (2016), que encontraram efeitos positivos de aumento de volume aéreo em indivíduos tratados com Hyrax híbrido com idade mais avançada (17 anos), que foram semelhantes aos resultados encontrados em indivíduos tratados com aparelhos dentossuportados com idade média de 14 anos. Cheung et al (2020), apresentaram também resultados positivos do Hyrax híbrido com relação ao aumento das vias aéreas superiores. Observou-se que pacientes na fase de pico de crescimento puberal apresentaram resultados melhores no aumento total das vias aéreas, quando comparado ao Hyrax e ao disjuntor Keles (dentossuportado).…”
Section: Discussionunclassified
“…Canan et al (2017), estudaram os efeitos da ERM por meio da sobreposição de modelos digitais, com os dispositivos Hyrax, Hyrax híbrido e MARPE (micro-implant asisted rapid palatal expansion), e mostraram que não houve diferenças com relação à inclinação dos dentes posteriores entre os três grupos avaliados. Cheung et al (2020), encontraram um maior aumento do volume aéreo em pacientes tratados com o Hyrax híbrido, quando comparados com pacientes tratados com dispositivos dentossuportados. Garib et al (2021), observaram maiores efeitos esqueléticos na cavidade nasal e nas dimensões da maxila, em pacientes tratados com o Hyrax híbrido.…”
Section: Lista De Figurasunclassified